(untitled) (Forum Penelitian Agro Ekonomi, 2016)
Regional autonomy gives more authority to the regional governments, namely those regencies and municipalities, to take the initiative in designing and developing a locally specific policy. It includes in conducting agricultural development in each region. The regional authorities in policy implementation have both positive and the negative impacts on agricultural development. Most of the regional governments’ regulations are designed to improve regional government revenues. Most regional government officials think that agricultural development is costly, but it takes a long time to return the investment. This is why issues of importance of agriculture are less attractive to the regional policymakers, especially in supporting agricultural business and extension. The positive impacts of regional autonomy can be observed in some regional governments successfully develop regional agricultural policy but not supported through the regional regulations.